2018
DOI: 10.1080/07853890.2018.1472389
|View full text |Cite
|
Sign up to set email alerts
|

Population-level seasonality in cardiovascular mortality, blood pressure, BMI and inflammatory cells in UK biobank

Abstract: The risk of CVD may be modulated by day length at temperate latitudes, and the implications of seasonality should be considered in all studies of human cardiometabolic health. Key messages In this cross-sectional study in UK Biobank, we report annual variations in cardiovascular risk factors and mortality that were associated with day length independent of environmental and lifestyle factors. These seasonal changes in day length might contribute to annual patterns in cardiovascular disease and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Low mood and anhedonia have been previously found to be higher in winter (Lyall et al, 2018) and we showed that insomnia has a similar pattern. Metabolic traits such as waist circumference, fat percentage, blood pressure, and BMI peak between January and March (Wyse et al, 2018) and we have shown that BMR accompanies these traits. We also showed that people generally rate themselves as having poor health in spring, after the peak period of metabolic traits.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Low mood and anhedonia have been previously found to be higher in winter (Lyall et al, 2018) and we showed that insomnia has a similar pattern. Metabolic traits such as waist circumference, fat percentage, blood pressure, and BMI peak between January and March (Wyse et al, 2018) and we have shown that BMR accompanies these traits. We also showed that people generally rate themselves as having poor health in spring, after the peak period of metabolic traits.…”
Section: Discussionsupporting
confidence: 67%
“…UK Biobank is a ~500 000 sample size adult community cohort study with detailed phenotype data. This cohort has already been used to show that low mood, anhedonia, body mass index (BMI), fat percentage, blood pressure, inflammation, and mortality related to cardiovascular problems are seasonal, with most peaking during winter months(Lyall et al, 2018; Wyse et al, 2018). However, seasonality of birth rate, basal metabolic rate (BMR), subjective health, and sleep have not been analyzed before in the UK Biobank.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal rhythms (Lincoln, 2019). Seasonal rhythms are evident in human behavior, metabolism, and immunity (Dopico et al, 2015;Lyall et al, 2018;Wyse et al, 2018), but it is not known if they are a response to climatic seasonal variations or if they represent an endogenous mechanism that would persist in constant conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal rhythms regulate reproductive, metabolic, behavioral, and immune function in animals at temperate clines, and this action across mammalian systems suggests that circannual timing mechanisms might have a ubiquitous presence in peripheral tissues, analogous to the circadian clock ( Lincoln, 2019 ). Seasonal rhythms are evident in human behavior, metabolism, and immunity ( Dopico et al., 2015 ; Lyall et al., 2018 ; Wyse et al., 2018 ), but it is not known if they are a response to climatic seasonal variations or if they represent an endogenous mechanism that would persist in constant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this burden is due to a combination of coronary artery disease (CAD), atrial fibrillation (AF), requiring long-term management in the community and episodic hospital admissions during periods of clinical instability [2] [3]. An important but often overlooked contributor to the growing burden of CVD worldwide is the phenomenon of "seasonality" characteristed by annual peaks and troughs in cardiovascular event rates coinciding with seasonal changes in climatic conditions and acute weather events [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%